Pembentukan Relasi Sosial Remaja Terlantar Melalui Bimbingan Kelompok Pada Kegiatan Meeting Morning - Adiansyah Adiansyah; Sri Maulidiana; M. Fadhil Yarda Gafallo (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The disconnection of children's opportunities to be educated in school and the neglect of children from the responsibilities of parents and families causes children to become displaced. The abandonment of children from a possive environment opens opportunities for children to get along and establish social relations in the wrong social environment. As the responsibility of the state to provide protection and social security to displaced children. the government is present by providing coaching and guidance through PSBR Yogyakarta. One of the activities given to abandoned children in PSBR Yogyakarta is the “morning meeting”. Through research conducted using qualitative methods, especially related to the formation of social relations through group guidance at “meeting morning” activities, the results of the child were obtained. Displaced shows a shy, minder, closed, temperamental attitude and has no concern for the surrounding environment. After undergoing a routine “meeting morning” activity, abandoned children show an open and more caring attitude in interacting with each other in a more positive and constructive. Negative attitude habits such as shyness, likes to cut off other people's speech and disrespect gradually began to diminish